Exploring Multi-Criteria Decision-Making for Academic Blockchain Platform Adoption - Aliu, Folasade; Bode, Moyinoluwa (Journal of Technology Management and Business, 2023)
A decentralised distributed ledger system called Blockchain Technology (BCT) enables safe, open, and impenetrable transactions without the need for a central authority. The technology was initially created for the Bitcoin cryptocurrency, but it has subsequently been applied to other areas such as voting procedures, supply chain management, and digital identity management. The technology is increasingly becoming accepted in the academic setting for a variety of purposes, including the creation and storage of academic records. There are numerous platforms accessible for this usage, though. When numerous decision-makers are engaged in the selection process, picking an appropriate platform can be a contentious affair. For decision makers, selecting among a wide range of acceptable options might be difficult. It is possible to overcome these difficulties by using Multi-criteria Decision-Making (MCDM) techniques. When there are numerous elements to take into account, one technique for making judgments is MCDM. The process entails assessing multiple options according to pre-established standards in order to identify the optimal selection. In essence, when there are several variables to consider, MCDM assists in selecting the option. The Fuzzy Analytic Hierarchy Process (FAHP) is one of the various MCDMs which this paper uses to choose the best BCT platform for academic records based on three choices (IBM, Ethereum, and Hyperledger Fabric) and five factors (cost, degree of acceptance, simplicity of use, data security, and level of customization). The analysis’s findings indicate that data security is the most crucial factor, with a weight of 0.645, and that IBM is the best BCT platform, with a value of 0.448. By comparing the FAHP results to those of AHP, IBM’s suitability as a platform was confirmed.